EDUKASI PENCEGAHAN ANEMIA PADA REMAJA - Hanifa, Fanni; Yolandia, Rita Ayu (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2025)
The World Health Organization (WHO) reports that the prevalence of anemia worldwide ranges between 40 and 88%, and about 53.7% of teenage girls in poor countries experience it. Anemia is one of the global health problems that needs attention, especially in developing countries like Indonesia. Kemenkes RI (2018) that 32% of adolescents aged 15 to 24 suffer from anemia, or 3 in 10 adolescents. The proportion of anemia in women is quite high (27.2%). Anemia can also affect teenage girls' learning performance, as anemia can lower learning concentration. Teenage girls with anemia are 1,875 times more likely to lower learning performance than teenagers without anemia. The dedication will take place on December 23, 2023 through Zoom meetings. The activities will be conducted through discussions, lectures, and questions. Education can enhance youth awareness of anemia prevention efforts in adolescents, both before and after education. Teenagers with good knowledge increased from 58.8% to 82.5%, while sufficient knowledge fell from 32.5% to 15%, and less knowledge decreased from 7% to 2%.